Analisis Pengaruh Pelatihan Dan Disiplin Kerja Terhadap Kinerja Karyawan - Marlinda, Indira Lulu, Dr. Edy Purwo SaputroSe., M.Si (2016)
This study aims to determine the effect of training and discipline on employee performance. The location of this research at Bank Rakyat Indoneisa (Persero) Tbk Branch Sragen. Research done taking a sample of 100 employees of Bank Rakyat Indonesia (Persero) Tbk Branch Sragen. While the methods used in this sampling is using questionnaire technique, with testing through the test of the validity of the method of confirmatory factor analysis, reliability testing with methods one shot, classical assumption (normality test, multicoloniarity, heteroscedasticity test and autocorrelation test), analysis multiple linear regression, and hypothesis testing (test t and f). Based on the analysis regarding the effect of the mix of human resources (training and discipline of work) on the performance of employees of Bank Rakyat Indonesia (Persero) Tbk Branch Sragen, all variables significantly influence employee performance. Keywords: Training, Discipline Work, Employee Performance